Dynamic changes of circulating miRNAs induced by the Ebola virus vaccine VSV-EBOV. Issue 46 (12th November 2018) - Fischer, T.; Spohn, M.; Olearo, F.; Zinser, M.E.; Kasonta, Rahel; Stubbe, H.C.; Rechtien, A.; Ly, M.L.; Schmiedel, S.; Lohse, A.W.; Grundhoff, A.; Addo, M.M.; et al.
Highlights: VSV-EBOV is the most advanced EBOV vaccine candidate in clinical development. VSV-EBOV induces a shared signature of circulating miRNAs in vaccinees. Early miRNA expression dynamics correlate with vaccine-induced immune responses. Circulating miRNAs might serve as biomarkers for vaccine-induced immunogenicity. The data provide novel insight into molecular mechanisms induced by VSV-EBOV. Abstract: VSV-EBOV is a replication-competent Ebola virus (EBOV) vaccine, which was tested in clinical trials as response to the Ebola virus disease (EVD) outbreak 2013–2016. It is the most advanced EBOV candidate currently in the licensure process. The experimental vaccine was again administered as response to outbreaks in the Democratic Republic of Congo. However, underlying molecular mechanisms that convey protection remain incompletely understood. MicroRNAs (miRNAs) are known key regulators that influence gene expression on a post-transcriptional level. The miRNA-mediated control has emerged as a critical regulatory principle in the immune system, which strongly influences the balance of innate and adaptive immune responses by modulation of signaling pathways critical for differentiation of immune cells. We investigated expression levels of circulating miRNAs (c-miRNAs) in plasma from healthy vaccinees, as they may reflect cellular dynamics following VSV-EBOV immunization and additionally may serve as potential biomarkers for vaccine efficacy. As part of the WHO-led VEBCON consortium, we investigated safety and immunogenicity of VSV-EBOV in a phase I trial. A comprehensive analysis of expression levels on c-miRNAs from plasma samples following VSV-EBOV immunization (day 0, 1, 3 post vaccination) was conducted using RT-qPCR assays. Potential biological relevance was assessed using in silico analyses. Additionally, we correlated dynamics of miRNA expressions with our previously reported data on vaccine-induced antibody and cytokine responses and finally evaluated the prognostic power by generating ROC curves. We identified four promising miRNAs (hsa-miR-146a, hsa-miR-126, hsa-miR-199a, hsa-miR-484), showing a strong association with adaptive immune responses, exhibited favourable prognostic performance and are implicated in immunology-related functions. Our results provide evidence that miRNAs may serve as useful biomarkers for prediction of vaccine-induced immunogenicity. Furthermore, our unique data set provides insight into molecular mechanisms that underlie VSV-EBOV-mediated protective immune responses, which may help to decipher VSV-EBOV immune signature and accelerate strategic vaccine design or personalized approaches.